Estimating the size of key populations for HIV in Singapore using the network scale-up method. (9th May 2019) - Teo, Alvin Kuo Jing; Prem, Kiesha; Chen, Mark I C; Roellin, Adrian; Wong, Mee Lian; La, Hanh Hao; Cook, Alex R
Abstract : Objectives: To develop a localised instrument and Bayesian statistical method to generate size estimates—adjusted for transmission error and barrier effects—of at-risk populations in Singapore. Methods: We conducted indepth interviews and focus group to guide the development of the survey questionnaire. The questionnaire was administered between July and August 2017 in Singapore. Using the network scale-up method (NSUM), we developed a Bayesian hierarchical model to estimate the number of individuals in four hidden populations at risk of HIV. The method accounted for both transmission error and barrier effects using social acceptance measures and demographics. Results: The adjusted size estimate of the population of male clients of female sex workers was 72 000 (95% CI 51 000 to 100 000), of female sex workers 4200 (95% CI 1600 to 10 000), of men who have sex with men 210 000 (95% CI 140 000 to 300 000) and of intravenous drug users 11 000 (95% CI 6500 to 17 000). Conclusions: The NSUM with adjustment for attitudes and demographics allows national-level estimates of multiple priority populations to be determined from simple surveys of the general population, even in relatively conservative societies.